Konsep Manajemen Kurikulum Lembaga Pendidikan Di SMAN 1 Ampek Angkek - Rina Andriyeni; Iswantir M (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The design, implementation, control (evaluation and refinement) of the curriculum, including who carries it out, when and where, are the areas of curriculum management. This research aims to outline the processes involved in creating a standardised curriculum management system and adapting it to the changing needs of society to foster a mutually beneficial partnership between the community and the school. The desk research model was the research methodology used. The results show that the curriculum management framework is based on the basic ideas of curriculum and learning management, organised as follows: school work programme, curriculum and learning planning, and curriculum and learning assessment.